ASSESSMENT OF READING COMPREHENSION SKILLS OF AMMUNITIONERS (American Journal of Interdisciplinary Research and Development, 2024)
This in the article in students developed speech of skills one is reading to understand skill evaluation about thought is conducted. In this of students by reading to understand skill evaluation text and about it Created to questions given answers through done is increased. To the test results According to his valid or invalid (ie really test students by reading to understand skill to evaluate valid or valid that it is not). is determined. Research in the end while of students common by reading to understand levels about conclusions is released.